Youth Participation in Formal Arenas of Politial Deliberation: from Adultocentrism to the Replication of Adult Speech - González Sancho, Roy (2016)
The following work encompasses the replication of discursive structures of adultcentrism in young people (18 to 35 years old). The results here presented correspond to various investigations from the program Agenda Joven in the years 2013 and 2014 in the framework of the Youths Political Electoral Observatory (OPEJ). Within this observatory, diverse participation areas in formal arenas have been analyzed. Hence, this article shows how the institutionalization of adultcentrism first permeates the structures of young people´s political participation and later constitutes a deeply rooted element in the dynamics of formal political practices for the youths involved in the electoral environment and the aspects estipulated by la Ley de la Persona Joven.